Transformative Learning to Resolve Grief among Bereaved Older Adults in Urban Indigenous Communities in South-South Nigeria - Ijah, Christiana N.; Patrick, John M. (NIU Journal of Social Sciences; Vol 9 No 1 (2023): NIU Journal of Social Sciences, Vol. 9 No. 1, March 2023, 2023)
This study examines how older adults resolved grief when bereaved of their spouse in urban indigenous communities in South-South Nigeria. The study was anchored on transformative learning theory by Mezirow. The study as guided by three research questions. Which are: What is the extent of grief among older adults on the loss of spouse? What are the effects of grieving among older adults who lost their spouse? How do older adults learn to resolve grief of bereavement of a spouse? The mixed research approach was adopted.  Questionnaire was use to collect quantitative data which were analyzed using descriptive statistics. Qualitative data were collected using semi-structured interview.  Using purposive sampling technique, 270 older adults from 65 years to 80 years in urban indigenous communities in Port Harcourt, Rivers State South-South Nigeria were selected. 210 were administered the questionnaire, but only 205 questionnaires were properly filled and returned while 60 persons were interviewed. The findings of the study were among that older adults inspect of their experiences about life, had very deep grief when their spouse died, that they suffer such effects like obsessive thinking, sleeplessness most of the times, extreme fatigue, weight loss, hallucination, numbness and shock on the death of their spouse, and that the degree of the effects of grieving varies and depends on the circumstances of the deceases. The study also reveals that the grieving process is in line with the transformative learning. It was concluded that that perspective transformation can occur among older adults following the death of their spouse. Keywords: Transformative learning, Grief, Bereavement, Older Adults,